Visions, provisions and reality: Political changes and education for democratic citizenship in Croatia - Spajić-Vrkaš, Vedrana (2003)
The paper is an attempt to describe and critically analyse the emergence and development of education that is directed at promoting citizens' empowerment and responsibility in the framework of political changes and democratic challenges that Croatia faces as a post-communist and post-war country within a prospect of European integration. In the beginning, a short reference to a politically unstable, economically extremely unfavourable and culturally complex context of education for democratic citizenship is given. Following the vision-provision-implementation-evaluation rationale for achieving the expected results, the author addresses the three main issues: the changes in the government's priorities for the period 1991-2001, with special emphasis on education ; the implementation measures that support educational changes pertinent to the quest for citizens' empowerment and their actual outcomes. The gap that exists between the visions and reality is explained as resulting from number of structural and psychological barriers that may be resolved through a more pronounced, coherent and co-ordinated development-oriented policy and implementation strategy based on consensus and commitment.
Projekt MZOS
Projekt MZOS
ENG